2023
DOI: 10.1590/1413-81232023287.14982022en
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with time-to-treatment initiation of breast cancer

Abstract: The present retrospective study investigated factors associated with time-to-treatment initiation of breast cancer of a cohort of 12,100 cases of health facilities qualified for high complexity in oncology within the scope of the Brazilian Public Health System (SUS) of Rio de Janeiro between 2013 and 2019. Multivariate logistic regression was used to estimate odds ratios and 95% confidence intervals. Of all cases, 82.1% were submitted to the first treatment >60 days. Patients without previous diagnosis hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Following further exclusions ( Fig. 1 ), 21 studies [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ] were eligible for inclusion in the review. The reference lists of these studies were then searched but no additional relevant studies were found.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following further exclusions ( Fig. 1 ), 21 studies [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ] were eligible for inclusion in the review. The reference lists of these studies were then searched but no additional relevant studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents the characteristics of the included studies. The majority (12) of studies [ [15] , [16] , [17] , 19 , 21 , 22 , 24 , 28 , 29 , 31 , 33 , 34 ] were cross-sectional, four were retrospective cross-sectional [ 18 , 25 , 32 , 35 ], four were prospective cohort [ 20 , 26 , 27 , 30 ] and one study was a before and after intervention study [ 23 ]. The duration of these studies varied from four months up to eight years, while two studies did not clearly mention the study duration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations